A born-translated fairy tale: transcultural readership and anti-exoticism in Robert Louis Stevenson’s “The Bottle Imp” (Altre Modernità, 2018)
The six years Robert Louis Stevenson spent in the Pacific region offer a particularly stark contrast with his received image as an uncommitted romancer (and hence, in the context of British colonialism, as a tacit supporter of imperialism). His Pacific writings are the work of a powerfully realist writer, with strong interests in ethnography and local history, engaged in the political life of the region, and an active supporter of the native populations in their opposition to imperial rule. In this article I focus on "The Bottle Imp", a short story that, at first sight, constitutes a less confrontational, more accommodating literary project if compared with most of Stevenson's production on the Pacific. However, not only does this text encapsulate several elements of the poetics that characterize Stevenson's Pacific writing, but it is also the only work of Stevenson's career to be conceived for a Polynesian audience, which adds a significant layer of complexity to its analysis. I argue that with this work Stevenson creates a "born-translated" fairy tale, which results in the adoption of specific narrative techniques and in a particular declination of Stevenson's political agenda and anti-exoticist strategies. This, in turn, means to frame "The Bottle Imp" within some of the current debates on the global circulation of literature and its effect on the politics, ethics and aesthetics of literary texts.